The uses of social investment - Hemerijck, A. (Anton) (Oxford : Oxford University Press, 2017)
The Uses of Social Investment provides the first study of the welfare state, under the new post-crisis austerity context and associated crisis management politics, to take stock of the limits and potential of social investment. It surveys the emergence, diffusion, limits, merits, and politics of social investment as the welfare policy paradigm for the 21st century, seen through the lens of the life-course contingencies of the competitive knowledge economy and modern family-hood. Featuring contributions from leading scholars in the field, the volume revisits the intellectual roots and normative foundations of social investment, surveys the criticisms that have leveled against the social investment perspective in theory and policy practice, and presents empirical evidence of social investment progress together with novel research methodologies for assessing socioeconomic 'rates of return' on social investment. Given the progressive, admittedly uneven, diffusion of the social investment policy priorities across the globe, the volume seeks to address the pressing political question as to whether the social investment turn is able to withstand the fiscal austerity backlash that has re-emerged in the aftermath of the global financial crisis.
Includes bibliographical references (pages 413-460) and index.
Keywords: Investments -- Moral and ethical aspects; Investments -- Social aspects; Welfare state; Investments -- Moral and ethical aspects; Investments -- Social aspects; Welfare state; Wohlfahrtsstaat; Sozialpolitik; Aufsatzsammlung